Effect Of Date Of Sowing On Alternaria Blight And Seed Yield Of Mustard (Journal of Plant Disease Sciences, 2018)
In India, mustard is the second most important edible oilseed after groundnut sharing 27.8% in the India’s oilseed economy. The oil of the rapeseed mustard is mainly used in human diet. The crop also has important place in industrial uses such as for manufacturing soap, paints, varnishes, hair oil, lubricants, textile auxiliaries and various other products. Indian mustard [Brassica juncea (L.) Czern and Coss.] is predominantly cultivated in Rajasthan, Uttar Pradesh, Haryana, Madhya Pradesh and Gujarat. Among these states, Rajasthan, Uttar Pradesh and Madhya Pradesh are the major rapeseed mustard growing states with 45.5%, 13.1% and 11.1% contribution, respectively, to the national acreage during the last five years. The corresponding contribution to production was 48.6%, 13.4% and 9.8%, respectively. In Madhya Pradesh mustard crop is cultivated in an area about 0.66 million ha with the production of 0.79 million tones and productivity of about 1192 kg/ha. The productivity of mustard in Tikamgarh district is very low (561 kg/ha) as compared to state average productivity. Though the area of the crop has increased 0.20 million ha (Anonymous, 2012).
Keywords: Date of sowing; Alternaria blight; Disease intensity; Yield; Mustard